(untitled) (Ibrahim Cardiac Medical Journal, 2023)
Background & Objective: Autism Spectrum disorder (ASD) is a developmental disorder that requires constant care by family members. Meeting the continuous care demand of the affected children takes a lot of time and effort. Studies have shown that parents of children with ASD experience heightened stress. The present study was intended to investigate the level of stress or burden of parents of children with ASD and to identify different psychiatric disorders among them. Methods: This cross-sectional study was conducted at Out Patient Department (OPD) of the Institute for Paediatric Neurodisorder and Autism (IPNA) in Bngobandhu Sheikh Mujib Medical University (BSMMU), Department of Psychiatry, BSMMU, Dhaka and Out-patient Department (Child Guidance Clinic), National Institute of Mental Health (NIMH), Sher-E-Bangla Nagar, Dhaka between January, 2015 to February, 2017. A total of 180 parents of children with ASD who voluntarily consented to participate in the study were included. Parents’ burden was assessed with the help of Bangla version Zarit Burden Interview 20 tool, which verifies the burden on caregivers who take care of people with mental and physical disabilities. The level of burden was operationalized and measured on a 0-4 Likert scale using 22 questions. Result: The mean age of the respondents (parents) was 36.2(range: 24-57) years with mothers being predominant (60%) in the sample. Nearly three-quarters (74.7%) of the mothers were housewife. The respondents on an average spent 60% of their time for caring their children. Thirty percent of the respondents had family history of mental illness. The mean duration of caring of children by the respondents was 6.1 years. In two-thirds of the respondents psychiatric disorders were also identified (15.6% were major depressive illness, 11.7% were dysthymic disorder, 8.9% panic disorder, 7.8% somatic symptoms disorder and 22% other disorders). About 44% of the respondents had moderate to severe burden, 35.6% mild to moderate burden and 16.1% severe burden. Younger parents were more likely to have moderate to severe and severe burden than their older counterparts (p = 0.048). Mothers tend to be associated with moderate to severe and sever burden more often than the fathers do (p < 0.001). Moderate to severe and severe burden demonstrated its significant presence among housewives than that among the other occupants (p = 0.028). Conclusion: The study concluded that parents who provide care to their child with ASD invariably suffer from stress or burden and a substantial proportion of them experience moderate to severe or severe burden requiring support to cope with the burden. Younger parents, mothers, particularly housewives are more likely to suffer from moderate to severe and severe burden. Ibrahim Card Med J 2022; 12 (1): 18-24